The Role Of Dincharya And Ritucharya In Healthy Lifestyle W.S.R. To Maintain The Biological Clock - Saini, Mukesh; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Today’s new world has rapidly emerged, that is, "Lifestyle Disorders." This world is basically related to chronic non-communicable diseases. In the current era, such non-communicable diseases have emerged in the form of epidemics. Ayurveda is an absolute lifestyle science. An ideal lifestyle has been described to maintain health. The lifestyle described puts an end to all changes that have occurred due to time. Ayurveda pays more attention to disease prevention rather than treatment. Therefore, it is not limited to disease management and treatment. As per present-day natural clock (circadian cadence) is an intrinsic instrument that controls the physiological exercises of an organic entity that change on every day, occasional, yearly, or another ordinary cycle. The circadian mood guideline assumes an essential part in individuals’ sound lives influenced by factors comprising of astronomical occasions identified with the universe and earth, natural variables (light, night and day term, and seasons), and ways of life. These components changes lead to aggravation of circadian musicality and it causes expanding the occurrence of mental sicknesses like wretchedness and physiological issues like malignant growths, cardiovascular infection, and diabetes. We as a whole vibe the back and forth movement of day-by-day life, the everyday rhythms that shape our days.